2017
DOI: 10.1016/j.ntt.2016.11.001
|View full text |Cite|
|
Sign up to set email alerts
|

Neonatal inhibition of Na + -K + -2Cl − -cotransporter prevents ketamine induced spatial learning and memory impairments

Abstract: Prolonged ketamine exposure in neonates at anesthetic doses is known to cause long-term impairments of learning and memory. A current theoretical mechanism explains this phenomenon as being neuro-excitotoxicity mediated by compensatory upregulation of N-methyl-D-aspartate receptors (NMDARs), which then initiates widespread neuroapoptosis. Additionally, the excitatory behavior of GABAergic synaptic transmission mediated by GABA A receptors (GABA A Rs), occurring during the early neuronal development period, is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
3
11
0
1
Order By: Relevance
“…The toxicity of sevo urane was demonstrated more intuitively at the cellular level. These results were similar to the ndings of many studies [19] .…”
Section: Most General Anaesthetics Are Excitants Of Gaba a R And Inhisupporting
confidence: 93%
See 1 more Smart Citation
“…The toxicity of sevo urane was demonstrated more intuitively at the cellular level. These results were similar to the ndings of many studies [19] .…”
Section: Most General Anaesthetics Are Excitants Of Gaba a R And Inhisupporting
confidence: 93%
“…receptor. Currently, relevant mechanisms have been shown, such as the hypothesis of neurotrophic apoptosis [2,3] , mitochondrial damage and accumulation of ROS [23] , the effect of in ammatory factors [16,24] , the excitatory neurotoxicity hypothesis [3] , the effects on the regeneration of neurons, changes in receptor subtypes [18] , and changes in ion concentration [19][20][21][22][23][24][25] . In our previous study, we found that sevo urane can induce neuroapoptosis in neonatal rats and cause behavioural changes during development, and that GABA A R played a role in sevo urane's neurotoxicity in the developing brain [18] .…”
Section: Most General Anaesthetics Are Excitants Of Gaba a R And Inhimentioning
confidence: 99%
“…Experimental evidence indicates that the NMDAR antagonist ketamine impairs cognition [19]. Prolonged ketamine exposure in neonates at anesthetic doses has been reported to cause long-term impairments of learning and memory [20]. Furthermore, ketamine decreased p-CREB in the hippocampus [21, 22], and decreased levels of BDNF [23].…”
Section: Discussionmentioning
confidence: 99%
“…Most general anaesthetics are excitants of GABA A R and inhibitors of the N-methyl-D-aspartate (NMDA) receptor. Currently, many studies demonstrated that neurotrophic apoptosis [2,3] , mitochondrial damage and accumulation of ROS [23] , in ammatory factors [16,24] , the excitatory neurotoxicity [3] , the effects on the regeneration of neurons, changes in receptor subtypes [18] were the possible mechanisms of general anaesthetics' neurotoxicity [19][20][21][22][23][24][25] . In the present study, we found that exposure of sevo urane caused neuron apoptosis and decreased cell vitality, which was consistent with the above conclusions.…”
Section: Discussionmentioning
confidence: 99%